Cloning and function prediction of full-length cDNA for cathepsin E derived from medaka (Oryzias latipes) - WANG Jiaqing; DONG Huiming; LI Zhengang; LI Shaoming; WANG Ruonan; FU Yujie (浙江大学学报. 农业与生命科学版, 2017)
Cathepsin is a kind of protease that mainly exists in intracellular lysosome. Under the weak acid condition, cathepsin can be activated and acts as hydrolysate protein. Based on the different mechanisms of the protein hydrolysis, cathepsin is divided into four species, including aspartic acid protease, cysteine protease, serine protease and threonine protease. Cathepsin D and cathepsin E (CtpE) both belong to aspartic proteases, while the latter is fundamental basis for life activities of mammals. Moreover, CtpE is an important enzyme in participating physiological processes of aquatic animals, such as digestion, yolk formation and immune response. However, few researches were focused on immune function of CtpE gene in fish.In this study, a full- length cDNA of CtpE was cloned from medaka (Oryzias latipes), to identify the gene and protein sequences of CtpE in medaka, and to clarify the evolutionary relationship of O. latipes CtpE (OlCtpE) with other animals, providing a theoretical foundation for further research on the physiological function of CtpE in fish.The total RNA was extracted from medaka gut tissue, using Trizol kit according to the manual steps. The quality of total RNA was extracted by agarose gel electrophoresis. Reverse transcription- polymerase chain reaction (RT - PCR) and rapid amplification of cDNA ends (RACE) were used to clone the full-length cDNA of OlCtpE from gut tissue in medaka. According to GenBank, the CtpE gene and corresponding protein sequence of Fundulus heteroclitus, Poecilia formosa, Austrofundulus limnaeus and Larimichthys crocea were downloaded and then analyzed through the global Clustal X alignment. The conserved region of the medaka OlCtpE gene fragment was amplified using the degenerate primers PF1 and PR1. The 3' RACE specific primers PE2 and PE3 were designed according to the conserved sequence, which was amplified by degenerate primers PF1 and PR1 using DNAStar software. The 5' RACE specific primers PE4, PE5 and PE6 were designed according to the conserved sequence, which was also amplified by degenerate primers PF1 and PR1 using DNAStar software. The RT - PCR product sequence, the 3' RACE and 5' RACE product sequences were assembled by using DNAman software. Clustal X 1.81 and MEGA 4.0 softwares were used to analyze the amino acid homology. The basic physical and chemical properties of proteins were predicted by ExPASy-PROSITE and ExPASy-ProtParam. The signal peptide and the glycosylation sites were predicted by SignalP 4.1 and NetNGlyc 1.0, respectively. The tertiary structure of OlCtpE protein was predicted by homology modeling method using SWISS-MODEL software.The results showed that the full-length cDNA of the OlCtpE was 1 301 bp, containing 24 bp 5'-untranslated regions (UTR), 56 bp 3'-UTR and 1 221 bp open reading frame, presumably encoding 406 amino acids. The cloned cDNA sequence of OlCtpE gene has been submitted to the GenBank database (accession number: KP864679). The N-terminus of OlCtpE protein contained a signal peptide of 17 amino acids, and it was a secretory protein. The OlCtpE protein contained three N-linked glycosylation sites,“NPTI”(amino acids 26-29),“NFSV”(amino acids 95-98) and “NLTV”(amino acids 162-165). The sequence homology from medaka CtpE protein was 77% with those of F. heteroclitus and A. limnaeus, 74% with that of P. latipinna, and 71% with that of L. crocea. A total of 22 CtpE proteins in different fish species had the active sites of conserved aspartate protease, which were “VIFDTGSSDLWV”(amino acids 98-109) and “AIVDTGTSLIAG”(amino acids 284-295) by homology analysis. The amino acid sequence homology was 43.60% between the CtpE protein from medaka and the porcine pepsinogen, and the two tertiary structures were also very similar. The tertiary structural analysis showed that the substrate was fixed to the active site in the active center, and the hairpin of the active site could provide space for the combination of substrate and enzyme. The overall shape of CtpE protein from medaka and porcine pepsinogen showed ellipsoid, and formed a relatively independent space entity.In conclusion, OlCtpE may play a very important role in the immune processing and presentation of exogenous antigen. Cloning and function analysis of the OlCtpE provide essential evidence for further studies on immune gene function.